A fly rhodopsin sheds light on thermal taste. (November 2020) - Stanley, Molly; McDowell, Sasha A.T.; Gordon, Michael D.
Abstract: In their recent paper, Li and colleagues discover that cold food tastes less sweet to flies, in part by activating bitter sensory neurons through a rhodopsin-dependent mechanism [1 ]. This work establishes temperature as an important variable in understanding fly taste processing and adds diversity to the sensory roles for rhodopsin receptors.